IQMA: cultivating the potential of the mind - Haron, Razali; Ibrahim, Nor Aini (Management Centre, IIUM, 2013)
The brain is the greatest gift from God. It has marveled thousands of brain experts worldwide but it has to be noted that the brain needs proper stimulation in order for it to perform to its maximum capacity. IQMA Training Sdn Bhd was established with this aim in mind, that is, to enhance human development through training to give the brain maximum stimulation. Both the right and left parts of the brain need to complement each other to produce a competent well rounded individual. Through the provision of training, IQMA hopes to develop emotionally and spiritually well-balanced competent individuals through its technique of using quick mental arithmetic calculation using the ten fingers and an abacus, aided by its human development modules. Nevertheless, being a tuition service by nature, IQMA needs to stand tall among its competitors in the industry.